Massive Shift in Gene Expression during Transitions between Developmental Stages of the Gall Midge, Mayetiola Destructor - Chen, Ming-Shun; Liu, Sanzhen; Wang, Haiyan; Cheng, Xiaoyan; El Bouhssini, M.; Whitworth, R. Jeff (My University, 2016)
Mayetiola destructor is a destructive pest of wheat and has six developmental stages. Molecular mechanisms controlling the transition between developmental stages remain unknown. Here we analyzed genes that were expressed differentially between two successive developmental stages, including larvae at 1, 3, 5, and 7 days, pupae, and adults. A total of 17,344 genes were expressed during one or more of these studied stages. Among the expressed genes, 38-68% were differently expressed between two successive stages, with roughly equal percentages of up-and down-regulated genes. Analysis of the functions of the differentially expressed genes revealed that each developmental stage had some unique types of expressed genes that are characteristic of the physiology at that stage. This is the first genome-wide analysis of genes differentially expressed in different stages in a gall midge. The large dataset of up-and down-regulated genes in each stage of the insect shall be very useful for future research to elucidate mechanisms regulating insect development and other biological processes.
Citation: Chen, M. S., Liu, S. Z., Wang, H. Y., Cheng, X. Y., El Bouhssini, M., & Whitworth, R. J. (2016). Massive Shift in Gene Expression during Transitions between Developmental Stages of the Gall Midge, Mayetiola Destructor. PLoS One, 11(5), 1-19. https://doi.org/10.1371/journal.pone.0155616
Keywords: Hessian Fly Diptera; Winter-Wheat; Cecidomyiidae Populations; Virulence; Cloning; Transcriptome